Differentiation of Human Embryonic Stem Cells into Neuron, Cholinergic, and Glial Cells. (27th November 2020) - Hosseini, Kimia; Lekholm, Emilia; Ahemaiti, Aikeremu; Fredriksson, Robert
Abstract : Human embryonic stem cells (hESCs) are pluripotent cells, capable of differentiation into different cellular lineages given the opportunity. Derived from the inner cell mass of blastocysts in early embryonic development, the cell self-renewal ability makes them a great tool for regenerative medicine, and there are different protocols available for maintaining hESCs in their undifferentiated state. In addition, protocols for differentiation into functional human neural stem cells (hNSCs), which have the potential for further differentiation into various neural cell types, are available. However, many protocols are time-consuming and complex and do not always fit for purpose. In this study, we carefully combined, optimized, and developed protocols for differentiation of hESCs into adherent monolayer hNSCs over a short period of time, with the possibility of both expansion and freezing. Moreover, the method details further differentiation into neurons, cholinergic neurons, and glial cells in a simple, single step by step protocol. We performed immunocytochemistry, qPCR, and electrophysiology to examine the expression profile and characteristics of the cells to verify cell lineage. Using presented protocols, the creation of neuronal cultures, cholinergic neurons, and a mixed culture of astrocytes and oligodendrocytes can be completed within a three-week time period.